Involvement in Self employment among Returnee Migrants in Chitwan - Tiwari, Pradip Raj (BMC Journal of Scientific Research, 2018)
Motivated by emerging issues of migration in Nepal, particular to returnee migrants, this paper examines the situation of returnee migrants and their participation in self employment based on cross-sectional data from 243 returnee migrants in three VDCs of Chitwan. The result shows that age, education, country of returned and re-migration plan are the major determinants of participation in self employment among returnee migrants where adult returnee migrants were more likely to engage in self employed compare to youth. The result also shows that the Gulf and Malaysian returnees who are not eager to migration again are more likely (odd ratio=2.645, p<0.01) to participate in self employment activities than those who returned from India. But, returnees from developed countries have no significant relation on participation in self employment. This study sheds light on a very important policy issue for Nepal particular to the economic development and participation in entrepreneurs’ activities of returnee migrants depends on country of return and their earning during the migration period. Thus, policies focusing on those returnee migrants are paramount for the development entrepreneur’s activities in the study area.